2014
DOI: 10.1145/2644865.2541980
|View full text |Cite
|
Sign up to set email alerts
|

Post-compiler software optimization for reducing energy

Abstract: Modern compilers typically optimize for executable size and speed, rarely exploring non-functional properties such as power efficiency. These properties are often hardware-specific, time-intensive to optimize, and may not be amenable to standard dataflow optimizations. We present a general post-compilation approach called Genetic Optimization Algorithm (GOA), which targets measurable non-functional aspects of software execution in programs that compile to x86 assembly. GOA combines insights from profile-guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Beyond these deployment issues, we also aim at extending this open testbed to consider other power-consuming components, such as GPU [54] and disk, in order to incrementally learn their power model and thus provide wider cartography of the power consumption of a software system. In the future, we believe that PowerAPI can be a cornerstone to new energy-aware scheduling [4,[15][16][17]19], to energyproportional computing [20][21][22][23], to new kind of optimizations [24], and to a better understanding of the power consumption drawn by software [25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond these deployment issues, we also aim at extending this open testbed to consider other power-consuming components, such as GPU [54] and disk, in order to incrementally learn their power model and thus provide wider cartography of the power consumption of a software system. In the future, we believe that PowerAPI can be a cornerstone to new energy-aware scheduling [4,[15][16][17]19], to energyproportional computing [20][21][22][23], to new kind of optimizations [24], and to a better understanding of the power consumption drawn by software [25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…23 inst_spec_exec_integer_inst counts the integer data processing instructions speculatively executed. 24 bus_cycles is not officially documented.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a preliminary investigation into using an energy model, but found that the potential for model inaccuracies can have significant negative impact. Specifically, using the model suggested by Schulte et al [155], we identified a variant of freqmine with over 70% predicted energy improvement, but only 2% actual improvement. To avoid misleading the search to such a significant degree, we decided to use physical measurements in our fitness function.…”
Section: Energy Measurementmentioning
confidence: 99%
“…We choose to manipulate programs written in assembly language. Assembly language is commonly available as a compiler output format [29], permits optimizations in the spirit of instruction scheduling [73] and superoptimization [82], and has previously been successfully used as the basis for post-compiler optimizations [155].…”
Section: Post-compiler Representationmentioning
confidence: 99%